2013
DOI: 10.4103/2249-4847.123089
|View full text |Cite
|
Sign up to set email alerts
|

Importance of normal values of CSF parameters in term versus preterm neonates

Abstract: Background:Evaluation of the cerebrospinal fluid (CSF) white blood cell (WBC) count and glucose and protein concentrations is used to assess the probability of the presence of central nervous system (CNS) infection. Although normal values are well established for CSF cell counts and protein and glucose contents in children and adults, this is not the case for neonates.Aims:The purpose of this study was to evaluate the composition of noninfected CSF obtained by nontraumatic lumbar puncture in neonates (age<28 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The CSF protein was examined as a covariate in this study as 50-55% of vancomycin is protein bound ( Schilling et al, 2011 ). As the CSF protein in a preterm baby is higher than that of a term infant, we hypothesised that this may have an effect on the unbound vancomycin in the CSF ( Majumdar et al, 2013 ; De Cock et al, 2017 ). However, no significant association was found between VI, CSF protein and CSF vancomycin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The CSF protein was examined as a covariate in this study as 50-55% of vancomycin is protein bound ( Schilling et al, 2011 ). As the CSF protein in a preterm baby is higher than that of a term infant, we hypothesised that this may have an effect on the unbound vancomycin in the CSF ( Majumdar et al, 2013 ; De Cock et al, 2017 ). However, no significant association was found between VI, CSF protein and CSF vancomycin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The presented free drug concentration might not accurately reflect the total vancomycin availability and longevity as it has been demonstrated that 50-55% of vancomycin is protein bound [21]. As the CSF protein levels in a preterm baby is higher than that of a term infant, this is an important factor that might influence the CSF vancomycin levels [22].…”
Section: Discussionmentioning
confidence: 99%
“…Counting of cells in sterile body fluids other than blood and urine, such as cerebrospinal fluid (CsF), peritoneal fluid (PeF), pleural fluid (PlF), synovial fluid (SyF), pericardial fluid (PrF),..etc provides important diagnostic information (1)(2)(3)(4). Elevated number of white blood cells (WBCs) can be a consequence or complication of a number of diseases.…”
Section: Introductionmentioning
confidence: 99%